Optimization of the Reading Corner Space as an Effort to Improve Primary School Students' Literacy Skills - Achmad Agil Nasarudin; Alicia Fatihah; Esqina Audiyah Sherine; Fitri Novita Erviana; Mudrikatus Soliha; Abdullah Kafabih (Business Finence Analyst Co.,, 2024)
Students' interest in reading literacy especially in elementary school has a low level, this problem is due to the lack of facilities available at school. This study aims to increase students' interest in reading literacy at SDN Karang Asem 1. The method used in this research is through the ABCD (Asset Based Communities Development) approach. The ABCD approach aims to maximize the potential of physical assets, individual assets, social assets and historical assets. The results of the study show that at SDN Karang Asem 1, there are several assets that have not been optimized, such as physical assets and individual assets. Another effort to maximize the potential of assets is by creating a reading corner and activities that can attract students' interest in reading, such as literacy educational games, adding trilingual vocabulary and ice breaking related to literacy education. Through the reading corner and these activities, it is hoped that it can increase the reading interest of Karang Asem 1 Elementary School students.